Carfilzomib plus dexamethasone in patients with relapsed and refractory multiple myeloma: A retro‐prospective observational study. (13th July 2022) - Del Giudice, Maria Livia; Gozzetti, Alessandro; Antonioli, Elisabetta; Attucci, Irene; Pengue, Ludovica; Cassano Cassano, Raffaella; Ghio, Francesco; Orciuolo, Enrico; Simoncelli, Martina; Bocchia, Monica; Galimberti, Sara; Buda, Gabriele
Abstract: Objective: We investigate safety and efficacy in common clinical practice of the combination of carfilzomib and dexamethasone (Kd56) approved for the ENDEAVOR trial for the treatment of relapsed or refractory multiple myeloma. Methods: We retro‐prospective analyzed 75 patients in three centers in Tuscany, 48 of whom had a clinically relevant comorbidity and 50 of whom were older than 65 years, treated with a median use in the fourth line of therapy. We assessed the efficacy based on the International Myeloma Working Group criteria. Results: The overall response rate was 60%. Median PFS was 10 months in the general cohort; in patients treated for more than 1 cycle of therapy PFS was 12 months. Quality of response to Kd56 treatment was found to positively impact PFS. Refractory status to previous line of therapy or to lenalidomide or an history of exposure to pomalidomide, seemed to have no impact on survival. We also showed a low adverse events rate, with no neuropathy events, and a relatively small number of cardiovascular events above grade 3 (10%). Conclusion: Kd56 is an effective and well tolerated regimen in highly pretreated and elderly patients with a good safety profile.